2010
DOI: 10.1080/14786410903335232
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of TNF-α induced NFκB activity by gallic acid and its semi-synthetic esters: possible role in cancer chemoprevention

Abstract: Gallic acid (3,4,5-trihydroxybenzoic acid), found in many plants either in free-form or part of tannins, is known to possess anti-microbial, antioxidant and cytotoxic properties. NFκB regulates the expression of several genes involved in carcinogenesis. These include anti-apoptotic, cytokines and cell cycle-regulatory genes. It is well established that the transcriptional factor NFκB is deregulated in many forms of cancer. Thus, agents that can suppress NFκB activation have the potential of suppressing carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Gallic acid represents a benzenoid compound found in many plants, either in the free-form or as part of tannins. This molecule is known to possess anti-microbial, antioxidant, and cytotoxic properties, and a previous study has shown that gallic acid was able to suppress TNF-α-induced NF-κB activity (Morais et al 2010). In vitro studies on the mode of action of gallic acid revealed that this compound interferes with the functioning of polymorphonuclear leukocytes, scavenging of superoxide anions, inhibition of myeloperoxidase release, and activity (Kroes et al 1992).…”
Section: Introductionmentioning
confidence: 94%
“…Gallic acid represents a benzenoid compound found in many plants, either in the free-form or as part of tannins. This molecule is known to possess anti-microbial, antioxidant, and cytotoxic properties, and a previous study has shown that gallic acid was able to suppress TNF-α-induced NF-κB activity (Morais et al 2010). In vitro studies on the mode of action of gallic acid revealed that this compound interferes with the functioning of polymorphonuclear leukocytes, scavenging of superoxide anions, inhibition of myeloperoxidase release, and activity (Kroes et al 1992).…”
Section: Introductionmentioning
confidence: 94%
“…The crude products were purified over a silica gel column eluted with mixtures of hexanes and EtOAc, furnishing alkyl gallates (compounds 2 to 16) ( Table 1). The molecular structures of these compounds were established by 1 H and 13 C nuclear magnetic resonance (NMR) spectral analysis (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic esters of gallic acid were prepared as described previously, with minor modifications (16,17). A 3.0-ml solution of N,N=-dicyclohexylcarbodiimide (DCC) (1.0 mmol) in dried p-dioxane was added to a cooled (5°C) solution of 0.2 mmol gallic acid (Sigma) (compound 1) (Table 1) and 20 mmol alkyl alcohol in 6.0 ml of dried p-dioxane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effects of JEZTC and GA on IL-1β-induced chondrocytes, the cells were grouped as follow: (1) normal control group, chondrocytes treated with culture medium only; (2) IL-1β (OA model) group, chondrocytes treated with culture medium contained 10 ng/ml IL-1β (Gibco, USA); (3) JEZTC-1 group, chondrocytes pre-incubated with 2.344 µg/ml JEZTC for 1 h followed by stimulation with IL-1β for 24 h; (4) JEZTC-2 group, chondrocytes pre-incubated with 4.688 µg/ml JEZTC for 1 h followed by stimulation with IL-1β for 24 h; (5) JEZTC-3 group, chondrocytes pre-incubated with 9.376 µg/ml JEZTC for 1 h followed by stimulation with IL-1β for 24 h; (6) GA group, chondrocytes pre-incubated with 4.688 µg/ml GA for 1 h followed by stimulation with IL-1β for 24 h. The concentrations of JEZTC were determined according to previous study [26]. The dose of GA was derived from the preliminary cytotoxicity assay, which was optimal for cell growth.…”
Section: Il-1β-induced Chondrocytes and Treatmentmentioning
confidence: 99%